Evaluation of A Nutrition Feeding Algorithm for Children and Adolescents Undergoing Haematopoietic Stem Cell Transplantation (HSCT) - Jodie, Bartle; Elise, McJannet; Natalie, T Whitehead; Heather, Gilbertson (International Journal of Nutrition, 2022)
Background Nutrition support during the acute phase post allogeneic haematopoietic stem cell transplantation (HSCT) is required to optimise short- and long-term outcomes for children. An algorithm was developed and evaluated to assist clinicians to make objective and consistent enteral feeding decisions. Methods The algorithm was evaluated on all patients who underwent allogeneic HSCT treatment between November 2017 - February 2019. Results Of the 48 patients, 43 had a nasogastric tube (NGT) inserted, of which 36 patients received a hydrolysed peptide-based formula, 5 patients received a whole protein formula only and 2 patients were fed an amino acid-based formula. Parenteral nutrition (PN) was used in 41 of the patients. Eleven did not have an NGT in-situ at the commencement of HSCT. Of the remaining 37 patients, 26 followed the algorithm and 11 patients did not comply. The group of patients who did not follow the algorithm had the longest median length of stay (LOS) of 49 days. Patients receiving only EN had the lowest median LOS of 30 days. The two groups that reported better weight outcomes were those who followed the algorithm and those who were fully EN fed. Conclusions Effective use of the HSCT feeding algorithm indicated improved patient outcomes for children undergoing HSCT, with better weight outcomes and reduced LOS. Recommendations to improve the efficacy and compliance of the algorithm include regular education/input to the oncology medical teams to better understand objective thresholds for EN and PN commencement.
Keywords: Nutrition; stem cell; children